Improving our legacy: Incorporation of adaptive management into state wildlife action plans - Fontaine, Joseph J. (Journal of Environmental Management)
The loss of biodiversity is a mounting concern, but despite numerous a ttempts there are few large scale conservation efforts that have prove n successful in reversing current declines. Given the challenge of bio diversity conservation, there is a need to develop strategic conservat ion plans that address species declines even with the inherent uncerta inty in managing multiple species in complex environments. In 2002, th e State Wildlife Grant program was initiated to fulfill this need, and while not explicitly outlined by Congress follows the fundamental pre mise of adaptive management, ‘Learning by doing’. When action is neces sary, but basic biological information and an understanding of appropr iate management strategies are lacking, adaptive management enables ma nagers to be proactive in spite of uncertainty. However, regardless of the strengths of adaptive management, the development of an effective adaptive management framework is challenging. In a review of 53 State Wildlife Action Plans, I found a keen awareness by planners that adap tive management was an effective method for addressing biodiversity co nservation, but the development and incorporation of explicit adaptive management approaches within each plan remained elusive. Only w25% of the plans included a framework for how adaptive management would be i mplemented at the project level within their state. There was, however , considerable support across plans for further development and implem entation of adaptive management. By furthering the incorporation of ad aptive management principles in conservation plans and explicitly outl ining the decision making process, states will be poised to meet the p ending challenges to biodiversity conservation.